Barriers to Study Enrollment in Patients With Advanced Cancer Referred to a Phase I Clinical Trials Unit. (23rd October 2013) - Fu, Siqing; McQuinn, Lacey; Naing, Aung; Wheler, Jennifer J.; Janku, Filip; Falchook, Gerald S.; Piha‐Paul, Sarina A.; Tu, Dennis; Howard, Adrienne; Tsimberidou, Apostolia; Zinner, Ralph; Hong, David S.; et al.
Learning Objectives: Assess barriers for advanced cancer patients to participate in phase I trials. Discuss strategies to improve the rate of enrollment of cancer patients in phase I trials. Abstract : Background: We conducted this retrospective study to identify reasons that patients referred to a phase I clinical trial failed to enroll or delayed enrollment onto the trial. Materials and Methods: Outcome analyses were conducted independently on data collected from electronic medical records of two sets of consecutive patients referred to a phase I clinical trial facility at MD Anderson Cancer Center. Data from the first set of 300 patients were used to determine relevant variables affecting enrollment; data from the second set of 957 patients were then analyzed for these variables. Results: Results from the two sets of patients were similar. Approximately 55% of patients were enrolled in a phase I trial. Patients referred from within MD Anderson were more likely to be enrolled than patients seen originally outside the institution ( p = .006); black patients were more likely than white patients to enroll (69% vs. 43%; p = .04). The median interval from the initial visit to initiation of treatments was 19 days. Major reasons for failure to enroll included failure to return to the clinic (36%), opting for treatment in another clinic (17%), hospice referral (11%), early death (10%), and lack of financial clearance (5%). Treatment was delayed for three weeks or more in 250 patients; in 85 patients (34%), the delay was caused by financial and insurance issues. Conclusion: Failure to return to the clinic, pursuit of other therapy, and rapid deterioration were the major reasons for failure to enroll; lengthy financial clearance was the most common reason for delayed enrollment onto a phase I trial. Abstract : This retrospective study was conducted to identify reasons that patients referred to a phase I clinical trial failed to enroll or delayed enrollment onto the trial. Approximately 55% of patients were enrolled on a phase I trial, and those referred from within MD Anderson were more likely to be enrolled than patients seen originally outside the institution. Major reasons for failure to enroll included failure to return to the clinic, opting for treatment in another clinic, hospice referral, early death, and lack of financial clearance.